Implementasi AI “Typing Speed Test” untuk membantu guru meningkatkan kemampuan mengetik siswa manajemen perkantoran - Dharma, Buyung Adi; Basuki, Andi; Churiyah, Madziatul; Sakdiyyah, Dewi Ayu (Nur Science Institute, 2024)
This service aims to improve digital teacher literacy through intensive training so that they can effectively implement the